UPAYA PENINGKATAN KESADARAN HUKUM PERLINDUNGAN KONSUMEN BAGI PELAKU USAHA ROSELLA KERING DESA SELOPANGGUNG, KABUPATEN KEDIRI - Miko Aditiya Suharto; Maria Novita Apriyani; Wiliandi Saputro (Jurnal Abdi Insani, 2023)
Dried rosella flower products are a business opportunity for the community. One of those who use this opportunity is a dried rosella flower business actor from Selopanggung Village, Kediri Regency. Many business actors who sell products from processed rosella flowers sometimes only pursue profit and therefore pay less attention to the quality of the products they sell. Conventional drying carried out on the side of the road is relatively exposed to dust and sand from the wind or from passing motor vehicles. Product management that is carried out without paying attention to the quality and quality of the product has the potential to have an impact on reducing consumers. Consumer protection law training is carried out with the aim of increasing the understanding of business actors so that they care about the quality and quality of traded commodities, considering that dried rosella will be brewed and drunk by the public. The research used in writing this scientific article is empirical juridical. The data collected is qualitative data. The research approach used in this writing uses a statute approach. Maintaining product quality and quality is a form of business actor's concern for consumers in accordance with Law 8/1999. Understanding of dried rosella flower business actors in Selopanggung Village regarding consumer protection laws can help business actors avoid potential economic and legal problems.